TEACHING VOCUBULARY AND ENGLISH DICTIONARY - Baxtiyorova Madina Baxrom qizi; Feruza Kucharova Alisher kizi (TADQIQOTLAR, 2025)
Abstract: Vocabulary acquisition is a fundamental part of learning any language, especially in English, which is widely spoken and used around the world. To effectively master vocabulary, learners should engage with a variety of strategies to not only remember the meanings of words but also understand their usage in different contexts. A rich vocabulary is crucial for both communication and comprehension in a second language. An essential part of vocabulary learning is the use of an English dictionary, which provides comprehensive definitions, examples, and even phonetic transcriptions of words. In addition, many dictionaries include information about word origins (etymology), synonyms, antonyms, and related forms of words, allowing learners to expand their vocabulary even further.